2021
DOI: 10.1080/0309877x.2021.1915967
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the experiences of the hidden curriculum of Black and minority ethnic undergraduate health and social care students at a London university

Abstract: An evaluation of the experiences of the hidden curriculum of Black and minority ethnic undergraduate health and social care students at a London university. Black and minority ethnic (BME) students are less likely to achieve a first or upper-class second degree than White students. This evaluation investigated the experiences of BME Health and Social Care students at a London university of the hidden curriculum, thematically analysed through a critical race lens. Four overarching themes were identified, (1) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The professor has bridged the gap for me... there were many things I was not familiar with because they were not taught to me. Dada is alluding to the hidden curriculum, which encompassed learning about racism as well as learning through relationships, the learning environment, social norms, values, beliefs, practices, and routines (Webb et al, 2022). Miller (2016 found that the hidden curriculum impacts students' feelings of belonging, their self-image and consequently their educational outcomes (cited in Webb et al, 2022).…”
Section: Journal Of Contemporary Issues Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The professor has bridged the gap for me... there were many things I was not familiar with because they were not taught to me. Dada is alluding to the hidden curriculum, which encompassed learning about racism as well as learning through relationships, the learning environment, social norms, values, beliefs, practices, and routines (Webb et al, 2022). Miller (2016 found that the hidden curriculum impacts students' feelings of belonging, their self-image and consequently their educational outcomes (cited in Webb et al, 2022).…”
Section: Journal Of Contemporary Issues Inmentioning
confidence: 99%
“…Dada is alluding to the hidden curriculum, which encompassed learning about racism as well as learning through relationships, the learning environment, social norms, values, beliefs, practices, and routines (Webb et al, 2022). Miller (2016 found that the hidden curriculum impacts students' feelings of belonging, their self-image and consequently their educational outcomes (cited in Webb et al, 2022). The Black faculty mentor, another woman, was critical in unpacking the racial capital of whiteness with Dada, as well as affirming her identity and navigating the institutional structures (Margolis & Romero, 2002;Webb, et al, 2022).…”
Section: Journal Of Contemporary Issues Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of competence, Webb et al (2022) examined the experience of the hidden curriculum; that is, the elements of learning that are generally unwritten, such as social norms and routines. BAME students report challenges with navigating complex enrolment processes (Webb et al, 2022). They reported having limited awareness of the value of good writing through use of grammar and other tools (Cousin & Cureton, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instead, appreciable messages about professionalism, rightness and wrongs, and the identities of clinicians are embedded in the very structure of medical work and the unique learning environment (Hafferty, 1998). More recent research (Mountford-Zimdars et al, 2015;Webb et al, 2021) highlights that the informal and hidden curriculum has an impact on students' sense of belonging, their self-image, and their interactions with teaching staff and peers, which play an important role in student academic performance.…”
Section: Cultural Competence Developmentmentioning
confidence: 99%